Foreign Exchange Reserves, Exchange Rate Regimes, and Monetary Policy: Issues in Asia - Akiko Terada-Hagiwara (Asian Development Review, 2005)
This paper seeks to outline issues arising from rapid foreign exchange reserve accumulations in Asia. Attention is paid to People’s Republic of China and India for the significance of the accumulation fed by surges in capital inflows. The paper finds that sterilization interventions by the two economies appear to be effective in curbing credit growth, but the impacts appear limited and short-lived. In this regard, adjustments of exchange rate policies are called for to have more freedom in policy options, though incentives to live with exchange rate fluctuations are still limited, and in fact the currencies have been managed more tightly than before. Therefore, the paper argues that, while maintaining the current exchange rate practices with capital controls in place, domestic reforms should be pushed further to be ready for capital account convertibility and more exchange rate flexibility in the long term.